5D BIM Implementation to Overcome Cost Management Issues in Upstream Oil and Gas Projects in Malaysia: A Review - Fathi, Mohamad Syazli; Ahmad, Azura (Journal of Technology Management and Business, 2024)
Since the COVID 19 strike, the upstream oil and gas industry has endured its darkest hours and longest stretch of low prices record. Due to the challenge posed by the volatility and uncertainty of the oil price, capital restraint and cost management will remain crucial for the sector in the future. To fight the cost overrun difficulties, oil and gas operators have implemented numerous strategies and mitigations, including cost reduction, prioritizing, or delaying projects, and tightening the supply chain and contracts. None, however, provides long-term viability and cost effectiveness.   Prior research on project cost overruns has indicated internal factors, notably the integration of project data,  as a major contributor to poor project performance resulted to cost overrun. However, no approaches or technologies have been proposed to improve cost management to control cost overruns. This paper aims to review the features and functions of 5D BIM which could contribute the integration of project data for the whole lifecycle and provide solution to the cost management issues in Malaysia's Oil and Gas Upstream Project.